Clinical features and prognosis of microscopic polyangiitis with usual interstitial pneumonia compared with idiopathic pulmonary fibrosis. (16th May 2019) - Zhao, Wen; Dai, Huaping; Liu, Yan; Zhu, Min; Bao, Na; Ban, Chengjun; Zhang, Shu; Ren, Yanhong; Ye, Qiao; Wang, Chen
Abstract: Introduction: Pulmonary involvement in microscopic polyangiitis (MPA) is common, little is known about the clinical features of MPA with interstitial pneumonia (MPA‐IP). Objectives: This study aimed to explore the prevalence of microscopic polyangiitis associated usual interstitial pneumonia (UIP)(MPA‐UIP) and compare its clinical features and prognosis with those of MPA‐non‐UIP and idiopathic pulmonary fibrosis (IPF). Methods: A total of 73 patients with MPA‐IP were identified and divided into MPA‐UIP patients and MPA‐non‐UIP patients. The clinical characteristics and survival of MPA‐UIP patients were analysed and compared with those of MPA‐non‐UIP patients and 68 patients with IPF. Results: The results showed that 34/73 (47%) MPA‐IP patients were classified as MPA‐UIP patients. Compared with MPA‐non‐UIP patients, MPA‐UIP patients tend to have longer duration of symptoms prior to diagnosis and usually have pulmonary involvement as the initial presentation. However, they were less likely to have proteinuria and/or hematuria. Compared with IPF patients, MPA‐UIP patients usually had multisystem damage, positive anti‐neutrophil cytoplasmic autoantibodies and elevated levels of nonspecific inflammatory markers. MPA‐UIP death was concentrated mainly in the first 3 months after diagnosis and resulted in a higher early mortality compared with IPF. Conclusion: UIP is the most frequent type of MPA‐IP. These patients tend to have longer duration of symptoms prior to diagnosis and usually have pulmonary involvement as the first presentation. However, they are less likely to have proteinuria and/or hematuria. MPA patients with UIP can be differentiated from IPF patients through comprehensive analysis of clinical and laboratory findings.